Train of the White Pass & Yukon Railroad on a trestle bridge leading to the tunnel between Heney Station and White Pass Summit, Alaska, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Tunnel on the White Pass and Yukon Route Alaska" Original image in Hegg Album 2, page 15. Original photograph by Eric A. Hegg 634; copied by Webster and Stevens 146.A.